Using Development-Oriented Equity Investment as a Tool for Restructuring Transition Banking Sectors - Meigas, Helo (World Bank, Washington, DC, 2014)
Over the past 10 years the three Baltic republics have undertaken significant restructuring of their banking sectors, supported by the World Bank through three projects: the Financial Institutions Development Project in Estonia, the Enterprise and Financial Sector Restructuring Project in Latvia, and the Enterprise and Financial Sector Project in Lithuania. These projects included a credit line, channeled through local commercial banks, to provide long-term funding and complementary technical assistance to private enterprises. In parallel, the government of Sweden injected equity into the commercial banks from Swedfund Financial Markets (SFM). The projects and the accompanying Swedfund equity were aimed at promoting sound banking systems in the three Baltic countries-by strengthening the equity in the banks and thereby expanding medium- and long-term financing. Meigas examines the role of SFM-which provides development-oriented equity investment (DEI) to Baltic banks-in the context of the World Bank programs. She examines the arguments for deploying DEI as a development vehicle by gauging its impact in the three Baltic countries on banking skills and services, on capitalization, and on shareholder structure and board membership. She draws out the role of technical assistance and compares its impact with that of DEI, and explores the possibilities offered by DEI for imposing sound corporate governance. The author also describes the necessary ingredients for successful DEI. The author's analysis shows that the Baltic projects were valuable initiatives that could in principle be replicated in other transition or developing economies whose banking sector faces serious restructuring challenges. A development-oriented equity investment, like that made by SFM, can address the important deficiencies in a banking sector that is still in a rudimentary state, lacking both capital and banking skills. SFM's most effective tool was the imposition of sound corporate governance on the institutions that received the equity injection. This approach provided a powerful supplement to the banking supervisory functions. Rather than relying on the external enforcement power of state supervision, SFM targeted internal processes to change business practices. As a result, the DEI led to improvements in the corporate culture and broader risk management and thus in the quality of banking services-not only meeting the institutional development objectives but also ensuring an adequate return on the invested capital. The potential of good corporate governance for easing the work of banking supervisors has been stressed by the Basle Committee on Banking Supervision. This potential is particularly valuable in countries still developing the supervisory function, and DEI, the author argues, is well suited for the task of improving corporate governance.